Strategi Komunikasi Pekerja Migran Indonesia dalam Mengatasi Culture Shock Selama Bekerja di Jepang - Athallah, Moch. Ahdan; Dharma, Ferry Adhi (UIN Raden Mas Said Surakarta, 2024)
This study aims to understand the communication strategies of Indonesian Migrant Workers (PMI) in overcoming culture shock while working in Japan. The research utilizes Anxiety Uncertainty Management Theory (AUM Theory) developed by Gudykunst to explain how PMI manage uncertainty and anxiety in cross-cultural communication. The AUM theory is elaborated with the concept of ABC's of Culture Shock by Ward Bochner and Furham to gain a comprehensive understanding of the relationship between cross-cultural communication and culture shock. The research method used is phenomenology. Data were collected through in-depth interviews with six PMI informants who have been working for at least two years in various companies in Japan. The results of the study show that PMI experience various forms of anxiety, including language anxiety, habit-related anxiety, and mindset-related anxiety. Workers manage this anxiety through three strategies: active, passive, and interactive. The active strategy involves continuously adapting to and appreciating Japanese culture. Firstly, the active strategy means that PMI actively seek information about Japanese culture through social media and study it. Secondly, the passive strategy involves self-motivation by understanding that the cultural surprises experienced are a consequence of their work. Lastly, the interactive strategy involves efforts to improve intercultural communication skills by joining Indonesian expatriate communities in Japan and being open to new values encountered while working in Japan.